Pre- and postnatal exposure of mice to concentrated urban PM2.5 decreases the number of alveoli and leads to altered lung function at an early stage of life - de Barros Mendes Lopes, Thais; Groth, Espen E.; Veras, Mariana; Furuya, Tatiane K.; de Souza Xavier Costa, Natalia; Ribeiro Júnior, Gabriel; Lopes, Fernanda Degobbi; de Almeida, Francine M.; Cardoso, Wellington V.; Saldiva, Paulo Hilario Nascimento; Chammas, Roger; Mauad, Thais (Environmental pollution (1987), 2018)
Gestational exposure to air pollution is associated with negative outcomes in newborns and children. In a previous study, we demonstrated a synergistic negative effect of pre- and postnatal exposure to PM2.5 on lung development in mice. However, the means by which air pollution affects development of the lung have not yet been identified. In this study, we exposed pregnant BALB/c mice and their offspring to concentrated urban PM2.5 (from São Paulo, Brazil; target dose 600 μg/m3 for 1 h daily). Exposure was started on embryonic day 5.5 (E5.5, time of placental implantation). Lung tissue of fetuses and offspring was submitted to stereological and transcriptomic analyses at E14.5 (pseudoglandular stage of lung development), E18.5 (saccular stage) and P40 (postnatal day 40, alveolarized lung). Additionally, lung function and cellularity of bronchoalveolar lavage (BAL) fluid were studied in offspring animals at P40. Compared to control animals that were exposed to filtered air throughout gestation and postnatal life, PM-exposed mice exhibited higher lung elastance and a lower alveolar number at P40 whilst the total lung volume and cellularity of BAL fluid were not affected. Glandular and saccular structures of fetal lungs were not altered upon gestational exposure; transcriptomic signatures, however, showed changes related to DNA damage and its regulation, inflammation and regulation of cell proliferation. A differential expression was validated at E14.5 for the candidates Sox8, Angptl4 and Gas1. Our data substantiate the in utero biomolecular effect of gestational exposure to air pollution and provide first-time stereological evidence that pre- and early life-postnatal exposure compromise lung development, leading to a reduced number of alveoli and an impairment of lung function in the adult mouse. [Display omitted] •Pre- and early postnatal exposure to PM2.5 lead to a decreased number of alveoli.•Pre- and early postnatal exposure to PM2.5 lead to increased lung elastance.•Gestational exposure to PM2.5 causes transcriptomic alterations in fetal lungs. This study is the first to provide comprehensive stereological and transcriptomic data in mice about the in utero effect of gestational exposure to PM2.5 on the fetal lung whilst demonstrating an impairment of alveolarization and lung function upon continued exposure to PM2.5 until an early stage of life.